2018
DOI: 10.1002/dys.1586
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and intentions of Greek teachers towards teaching pupils with dyslexia: An application of the theory of planned behaviour

Abstract: The present study aims to examine Greek public primary school teachers' attitudes and intention towards teaching pupils with dyslexia using a model of the theory of planned behaviour (TPB). Toward that aim, 304 teachers aged between 22 and 59 years old, with an average overall work experience of 16.6 years completed a TPB questionnaire which assessed their attitudes, subjective norms and perceived behavioural control, their intention, as well as other exogenous factors. The validity and the reliability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
(46 reference statements)
0
7
0
1
Order By: Relevance
“…DYTÖ'nün güvenirliği Cronbach alfa iç tutarlık katsayısı ile incelendiğinde hesaplanan iç tutarlık katsayılarının .84 ile .93 arasında değiştiği görülmüştür. Güvenirlik katsayısı için esas alınması önerilen ölçüt .70 ve yukarısı olduğundan, elde edilen katsayılar güvenirlik için yeterli kabul edilmektedir (Sipahi, Yurtkoru ve Çinko, 2010). Buna göre, DYTÖ'nün güvenilir ölçümler üreten bir ölçme aracı olduğu ifade edilebilir.…”
Section: Tartışma Ve Sonuçunclassified
“…DYTÖ'nün güvenirliği Cronbach alfa iç tutarlık katsayısı ile incelendiğinde hesaplanan iç tutarlık katsayılarının .84 ile .93 arasında değiştiği görülmüştür. Güvenirlik katsayısı için esas alınması önerilen ölçüt .70 ve yukarısı olduğundan, elde edilen katsayılar güvenirlik için yeterli kabul edilmektedir (Sipahi, Yurtkoru ve Çinko, 2010). Buna göre, DYTÖ'nün güvenilir ölçümler üreten bir ölçme aracı olduğu ifade edilebilir.…”
Section: Tartışma Ve Sonuçunclassified
“…The researchers used this theory to explore the teachers' experiences with dyslexic learners in mainstream classrooms. Stampoltzis et al (2018) used the theory and found that the teachers' intention towards teaching dyslexic pupils is predicted by the three determinants of behavioural intention.…”
Section: Theoretical Background Of the Studymentioning
confidence: 99%
“…Knight (2018) revealed that teachers lacked the knowledge of the biological and cognitive aspects of learners with dyslexia and further demonstrated the relevance of good quality teacher training in increasing teachers' confidence working with such category of learners. Stampoltzis et al (2018) observed that teachers faced several barriers and express neutral to positive attitudes to dyslexia. Leseyane et al (2018) revealed that teachers in public schools used negative comments that embarrassed dyslexic learners and offered no extra attention to them.…”
Section: Review Of Related Empirical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusive educational settings should satisfy the diverse needs of all learners in terms of offering an individualized approach and differentiated instructional practices to support learning (Forlin, 2013;Frederickson & Cline, 2002;Košak-Babuder, Kormos, Ratajczak, & Pižorn, 2019;Loreman, Deppeler, & Harvey, 2011). Securing full participation in mainstream schooling for every student requires knowledgeable, well-trained and responsive teachers (Bae, Yin, & Joshi, 2019;Fuchs, Kahn-Horwitz, & Katzir, 2019;Kwok-Shing Wong & Russak, 2020) who can accommodate the needs of all learners (Stampoltzis, Tsitsou, & Papachristopoulos, 2018). This, in turn, cannot be achieved without appropriate inclusive teacher training and teacher preparedness for inclusion (Coady, Harper, & de Jong, 2016;European Agency for Development in Special Needs Education, 2012;Forlin, 2010Forlin, , 2012Hettiarachchi & Das, 2014;Robinson, 2017;Sharma, Forlin, Deppeler, & Guang-xue, 2013;Woodcock, 2020).…”
Section: Introductionmentioning
confidence: 99%